The Best Years of Our Lives - William Wyler; Loy, Myrna; Fredric March; Dana Andrews; Teresa Wright; Virginia Mayo; Cathy O'Donnell; Hoagy Carmichael; Harold Russell; Gladys George; Roman Bohnen; Ray Collins; et al. (USA MGM, 1946)
The story concentrates on the social re-adjustment of three World War II servicemen, each from a different station of society. Al Stephenson (Fredric March) returns to an influential banking position, but finds it hard to reconcile his loyalties to ex-servicemen with new commercial realities. Fred Derry (Dana Andrews) is an ordinary working man who finds it difficult to hold down a job or pick up the threads of his marriage. Having had both hands burnt off during the war, Homer Parrish (Harold Russell) is unsure that his fiancée's feelings are still those of love and not those of pity. Each of the veterans faces a crisis upon his arrival, and each crisis is a microcosm of the experiences of many American warriors who found an alien world awaiting them when they came marching home. In short, the film has everything: laughter, tears, romance, anger, compassion, steadfast love, wrenching drama, social message, emotional dynamite.
Samuel Goldwyn's greatest production
Keywords: Drama -- American Corner; Romance